Dietary Cholest-4-en-3-one, a Cholesterol Metabolite of Gut Microbiota, Alleviates Hyperlipidemia, Hepatic Cholesterol Accumulation, and Hyperinsulinemia in Obese, Diabetic db/db Mice - Mina Higuchi; Mai Okumura; Sarasa Mitsuta; Bungo Shirouchi (Metabolites, 2024)
Previous studies have shown that dietary cholest-4-en-3-one (4-cholestenone, 4-STN) exerts anti-obesity and lipid-lowering effects in mice. However, its underlying mechanisms are not fully understood. In the present study, we evaluated whether 4-STN supplementation would protect obese diabetic db/db mice from obesity-related metabolic disorders. After four weeks of feeding of a 0.25% 4-STN-containing diet, dietary 4-STN was found to have significantly alleviated hyperlipidemia, hepatic cholesterol accumulation, and hyperinsulinemia; however, the effect was not sufficient to improve hepatic triglyceride accumulation or obesity. Further analysis demonstrated that dietary 4-STN significantly increased the content of free fatty acids and neutral steroids in the feces of db/db mice, indicating that the alleviation of hyperlipidemia by 4-STN was due to an increase in lipid excretion. In addition, dietary 4-STN significantly reduced the levels of desmosterol, a cholesterol precursor, in the plasma but not in the liver, suggesting that normalization of cholesterol metabolism by 4-STN is partly attributable to the suppression of cholesterol synthesis in extrahepatic tissues. In addition, dietary 4-STN increased the plasma and hepatic levels of 4-STN metabolites cholestanol (5α-cholestan-3β-ol) and coprostanol (5β-cholestan-3β-ol). Our results show that dietary 4-STN alleviates obesity-related metabolic disorders, such as hyperlipidemia, hepatic cholesterol accumulation, and hyperinsulinemia, in db/db mice.